Zasoby wodne województwa dolnośląskiego w okresach suszy = Water resources assessment during drought period in Dolnośląskie Province region - Tokarczyk, Tamara; Adynkiewicz-Piragas, Mariusz; Bogusz, Anna; Otop, Irena; Urban, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Dolnośląskie Province is the one of the poorest region in water supply in the whole territory of Poland. The crucial role for hydrological conditions plays precipitations and also their temporal and spatial distribution in Odra basin. The natural reason of low flow in rivers is river supply scarcity which is caused by precipitations lack and increasing of evaporation. The lack precipitation caused that rivers are supply by only groundwater. In summer season when high temperatures help to evaporation increasing water supply are decreased. Water resources in such periods are gradually bailing. It can lead to appearance breaks in water demand for all users. In this paper water resources were assessed on the basis of low flow periods in rivers Dolnośląskie Province territory and described their deficit volume and duration.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zasoby wodne; susza; niżówki; water resources; drought; low flow